(untitled) (Prithvi Academic Journal, 2022)
This paper aims to explore the impact of agricultural self-sufficiency that can ensure a sustainable economic development in Nepal. To meet this objective, the paper has adopted the descriptive-analytical research method. The required data for this study have been taken from the secondary sources, mainly journal articles. During the study period from FY2016/17 to FY2018/19, the production in cereal crops has been increasing slowly, but the yield is found improving from 2.79 to 3.10 M.T./hector and in the case of cash crops, the productivity is found to be the highest during the study period. It has increased from 12.77 to 13.04 M.T./hector. Nepal is enriched with agro-diversity and the economy has ample resources for the production of all food grains. If there is no efficiency in agricultural production, the economy should import food grains to supply needy people. So, it is important to be self-sufficient economy in agricultural food grains and to drive economic growth by increasing production and productivity.